2013
DOI: 10.1111/plb.12123
|View full text |Cite
|
Sign up to set email alerts
|

Gravity‐dependent differentiation and root coils in Arabidopsis thaliana wild type and phospholipase‐AI knockdown mutant grown on the International Space Station

Abstract: Arabidopsis roots on 45° tilted agar in 1-g grow in wave-like figures. In addition to waves, formation of root coils is observed in several mutants compromised in gravitropism and/or auxin transport. The knockdown mutant ppla-I-1 of patatin-related phospholipase-A-I is delayed in root gravitropism and forms increased numbers of root coils. Three known factors contribute to waving: circumnutation, gravisensing and negative thigmotropism. In microgravity, deprivation of wild type (WT) and mutant roots of gravise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
3
14
0
1
Order By: Relevance
“…In agreement with our previous results (Reginato et al 2014), P. strombulifera showed a greater sensitivity to Na 2 SO 4 than to NaCl, as indicated by the important oxidative damage induced in tissues when the SO 4 2− anion is present in the medium. Malondialdehyde is considered a reliable indicator of oxidative stress resulting from degradation of membrane lipids under several abiotic constraints (Zhang and Kirkham 1996; Hernández et al 2001).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our previous results (Reginato et al 2014), P. strombulifera showed a greater sensitivity to Na 2 SO 4 than to NaCl, as indicated by the important oxidative damage induced in tissues when the SO 4 2− anion is present in the medium. Malondialdehyde is considered a reliable indicator of oxidative stress resulting from degradation of membrane lipids under several abiotic constraints (Zhang and Kirkham 1996; Hernández et al 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Stimulation of shoot growth at Ψ o values up to −1.9 MPa (500 mM) NaCl is an interesting halophytic response found in our studies (Reginato et al 2014). Findings in other Prosopis species indicate that the NaCl tolerance of P. strombulifera exceeds the limits described for most halophytic plants (Catalán et al 1994; Almeida Viégas et al 2004; Felker 2007).…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Genetic studies of the secretory phospholipase А 2 β in relation to the auxin sensitivity of its gene expression indicated that the enzyme is needed for stem and hypocotyl gravitropism and auxin action during gravity response (Lee et al 2003). A knockdown mutant of patatin-related phospholipase A-I (ppla-I-1) was shown to have delayed gravitropic responses in roots, hypocotyls, and flower stalks (Scherer and Pietrzyk 2014). A possible reason for this is that the enzyme mediates auxin-induced gene expression (Effendi et al 2014).…”
Section: Phospholipase Amentioning
confidence: 98%